FREQUENCY OF TOXOPLASMA GONDII IN CATS IN METOPOLITAN LIMA AND CONCORDANCE BETWEEN INDIRECT IMMUNOFLUORESCENCE AND INDIRECT HAEMAGLUTINATION TECHNIQUES - Cerro T., Luis (2009)
The aim of the present work was to estimate the frequency of antibodies anti- Toxoplasma gondii in cats of Lima city, and to determine the rate of concordance between the Indirect Immunofluorescence (IFI) and Indirect Haemaglutination (HAI) assays. A total of 178 cat serum samples were collected in veterinary clinics of varios districts of Lima. The results showed 11.2 ± 4.6% (HAI) and 17.9 ± 5.6% (IFI) positive serums to T. gondii, and without statiscal differences due to sex and age group. The Kappa (K) value was 0.73 indicating a substantial concordance between the two assays indicating that both assays can be reciprocally replaced.